PENGARUH NILAI TUKAR (KURS) RUPIAH DAN TINGKAT INFLASI TERHADAP HARGA SAHAM PADA SUB-SEKTOR PERBANKAN DI BURSA EFEK INDONESIA (BEI) - Tiur Novi Rossy; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Monetary situation and macroeconomic variables movement are things that must be considered by an investor in doing stock trading activity in a country. The state of the economy and the fluctuation of macro variables in a country can affect the stock price, including in the banking sector. This study aims to examine the effect of macroeconomic variables namely exchange rate (exchange rate) and inflation rate to stock price. This research uses quantitative method. The population in this study are all banking companies listed on the Indonesia Stock Exchange (BEI) inthe period 2011-2015.This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Based on predetermined criteria, 9 banking companies were selected as samples in this study. The classical assumption test in this research includes normality test, multicollinearity test, heterokedastisity test and autocorrelation test. Data analysis using multiple linear regression analysis, t test, F test, and test of coefficient of determination.Data analysis using multiple linear regression analysis with SPSS 16.The results of this study indicate that the variable exchange rate (exchange rate) and partial inflation rate (t test) does not affect the stock prices of sub-sector companies listed on the Indonesia Stock Exchange. Simultaneous test results (f) show no influence of variables exchange rate (exchange rate) and inflation rate on stock prices in the banking sub-sector listed on the Indonesia Stock Exchange.Keywords: Exchange Rate, Inflation Rate, Stock Price.